INVESTIGATION OF PHYSICOCHEMICAL AND MECHANICAL CHARACTERISTICS OF STEEL AND CAST IRON CHIPS - O. M. Dyakonov (Литьë и металлургия)
The chemical and phase composition of steel and cast iron chips is studied, quantitative content of phases, including ferric oxides and other chemical elements chips, is determined.